(untitled) (CIPEEX, 2025)
This study addresses the legal treatment of negligent homicide in traffic caused by reckless conduct, as provided by the Brazilian Traffic Code (CTB) and the Penal Code. Considering the high number of fatal traffic accidents and discussions about the effectiveness of current penalties, the research aims to evaluate the (un)necessity of reclassifying applicable sanctions for this type of crime. Through a qualitative approach and document analysis, the work examines the difference between eventual intent and conscious negligence, the practical application of penalties, and the effectiveness of sanctions in ensuring the educational and punitive nature of sentences. The results suggest that current legislation may not fully meet social expectations of justice and prevention, indicating the importance of public policies and more intensive enforcement to reduce traffic accidents.